Reactive Astrocytes in Central Nervous System Injury: Subgroup and Potential Therapy - Yu, GuiLian; Zhang, Ying; Ning, Bin (Frontiers in Cellular Neuroscience, 2021)
Traumatic central nervous system (CNS) injury, which includes both traumatic brain injury (TBI) and spinal cord injury (SCI), is associated with irreversible loss of neurological function and high medical care costs. Currently, no effective treatment exists to improve the prognosis of patients. Astrocytes comprise the largest population of glial cells in the CNS and, with the advancements in the field of neurology, are increasingly recognized as having key functions in both the brain and the spinal cord. When stimulated by disease or injury, astrocytes become activated and undergo a series of changes, including alterations in gene expression, hypertrophy, the loss of inherent functions, and the acquisition of new ones. Studies have shown that astrocytes are highly heterogeneous with respect to their gene expression profiles, and this heterogeneity accounts for their observed context-dependent phenotypic diversity. In the inured CNS, activated astrocytes play a dual role both as regulators of neuroinflammation and in scar formation. Identifying the subpopulations of reactive astrocytes that exert beneficial or harmful effects will aid in deciphering the pathological mechanisms underlying CNS injuries and ultimately provide a theoretical basis for the development of effective strategies for the treatment of associated conditions. Following CNS injury, as the disease progresses, astrocyte phenotypes undergo continuous changes. Although current research methods do not allow a comprehensive and accurate classification of astrocyte subpopulations in complex pathological contexts, they can nonetheless aid in understanding the roles of astrocytes in disease. In this review, after a brief introduction to the pathology of CNS injury, we summarize current knowledge regarding astrocyte activation following CNS injury, including a) the regulatory factors involved in this process; b) the functions of different astrocyte subgroups based on the existing classification of astrocytes; and c) attempts at astrocyte-targeted therapy.